Origin and evolution of coastal lagoons from the Pampean region: Mar Chiquita, Las Brusquitas, Reta - Federico Ignacio Isla; José Bedmar; Camilo Vélez Agudelo; Luis Cortizo (Latin American Journal of Sedimentology and Basin Analysis, 2023)
Low-lying coasts are specially conditioned for the origin and development of coastal lagoons. The Pampean region (Buenos Aires, Argentina) contains the surplus of a sea level fluctuation that occurred during the last 6000 years. This report studied three coastal lagoons at different stages of their evolution: Mar Chiquita coastal lagoon, Las Brusquitas estuarine lagoon, and the small coastal lagoon of Balneario Reta. The long-term evolution is considered in the case of Mar Chiquita and Las Brusquitas, while modern trends are also described for the Mar Chiquita silting problems and the urbanisation of the Reta village surrounding the lagoon. The study is based on radiocarbon datings, salinity analyses and sedimentological studies on both outcrops and piston cores.